Icelandic academic word list - Pálsdóttir, Auður; Ólafsdóttir, Sigríður (Menntavísindasvið Háskóla Íslands, 2023)
In Iceland and elsewhere, there is an increased awareness of the key role that vocabulary plays in learners’ literacy development (Auður Pálsdóttir, 2017; Beck et al., 2013; Roessingh, 2016; Sigríður Ólafsdóttir & Baldur Sigurðsson, 2017). The academic words vused across different subject areas (Tier 2) are pivotal for students’ academic procedures (DiCerbo et al., 2014; Lawrence et al., 2016).The purpose of this research was to develop a Tier 2 Icelandic academic word list (í. listi yfir íslenskan námsorðaforða, LÍNO-2). Such a list is important since it provides information about Icelandic words that learners need to know for active participation in school, their reading comprehension, discussion and writing skills.In the Icelandic language, the number of words is countless, and therefore, it is important to know what words lie at the heart of academic success. Thus, it is v to research which words and how many words are useful to work with at each education level. Words that go beyond the most common words of the language (Tier 1) are called academic vocabulary (Beck et al., 2013; Roessingh, 2016). A part of these words is taught systematically within the various school subjects. Those are Tier 3 words. However, the words in Tier 2 are often overlooked by teachers and neglected in school activities. Words in this category are general, high-utility academic words used across various fields of study. They play a key role when discussing complex issues. The learners’ poor knowledge of these words is one of the main reasons why they have difficulty understanding a written text, which in turn, reduces their ability for academic progress.A new Icelandic corpus (Málheild fyrir íslenskan námsorðaforða, MÍNO) was compiled containing selected student and academic texts from Tagged Icelandic Corpus (MÍM, Stofnun Árna Magnússonar í íslenskum fræðum, n.d.-a) and Icelandic Gigaword Corpus (IGC, Stofnun Árna Magnússonar í íslenskum fræðum, n.d.-b). MÍNO has a total of 31,680,235 running words. All the texts are current ...